EKSPLORASI KURIKULUM PENDIDIKAN PANCASILA DALAM MEMBENTUK KESADARAN POLITIK KRITIS DAN ETIKA BERDEMOKRASI BAGI PEMILIH PEMULA BERDASARKAN KONTEKS KONSTITUSIONAL INDONESIA - Permana, Gilang; Hermanto, Odang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila Education plays a crucial role as an ideological foundation in shaping critical political awareness and democratic ethics for first-time voters in Indonesia. This study explores how the Pancasila Education curriculum is integrated to strengthen the younger generation's understanding of constitutional rights and obligations within the democratic system. Through a qualitative approach using literature studies on the constitutional framework and national education policy, this study analyzes the urgency of internalizing Pancasila values as a filter in facing the challenges of disinformation and political polarization in the digital era. The results show that a curriculum focused solely on theoretical rote learning is not effective enough to build critical reasoning. A transformation of learning based on deliberative practice and ethical political participation simulations is required to ensure that first-time voters are not merely objects of votes, but intelligent, polite, and responsible political subjects. By referring to constitutional values, this education aims to create an inclusive and substantive democratic ecosystem. These findings emphasize that the reorientation of the Pancasila Education curriculum must prioritize open dialogue and critical analysis of current national issues.